Hubungan Pembelajaran Scaffolding dengan Keterampilan Sosial Anak Usia 5-6 Tahun di TK Dharma Tunas Kekar Banyuasin - Padilah Padilah; Rizki Novtria (Departement of Mathematics Education, 2023)
This research focuses on students' understanding of the learning tools to be used before conducting Field Experience Practice (PPL). This study aims to determine students' understanding of learning tools before conducting Field Experience Practice (PPL). The type of research used in this study is descriptive with a qualitative approach. The research subjects used are students at the Faculty of Teacher Training and Education who are taking PPL courses. Data collection techniques are carried out with objective tests. The data analysis technique is carried out using a percentage formula with the test instruments covering five learning device components. From the total number of respondents who answered the objective question test, scores were obtained in the range of 20-40. The average of the total student test scores was obtained with a score of 27.86 with the criteria of not being ready to carry out PPL. Collaboration in related courses is needed before PPL is carried out in the form of seminars and direct assistance related to the preparation of learning tools so that students better understand the material other than those obtained in lectures.